Steam co-gasification of brown seaweed and land-based biomass - Kaewpanha, Malinee; Guan, Guoqing; Hao, Xiaogang; Wang, Zhongde; Kasai, Yutaka; Kusakabe, Katsuki; Abudula, Abuliti (Fuel processing technology, 2014)
Alkali and alkaline earth species in biomass have self-catalytic activity on the steam gasification to produce hydrogen-rich gas. In this study, three types of biomass, i.e., brown seaweed, Japanese cedar, apple branch containing different concentrations of alkali and alkaline earth species, and the mix of both of them were gasified with steam in a fixed-bed reactor under atmospheric pressure. The effects of reaction temperature, steam amount and mixing ratio in co-gasification on gas production yields were investigated. The results showed that higher gas production yields (especially for H2 and CO2) were obtained when the brown seaweed was used than the other two types of biomass since the ash content in brown seaweed was much higher than in land-based biomass and contained a large amount of alkali and alkaline earth species. The yield of hydrogen increased with an increase in the amount of steam, but excessive steam use reduced the hydrogen production yield. From the co-gasification experiments, the gas production yields (especially for H2 and CO2) from the land-based biomass increased with the increase in brown seaweed ratio, suggesting that the alkali and alkaline earth species in brown seaweed acted as the catalysts to enhance the gasification of land-based biomass in co-gasification process.